Innovative Transformation of S-Box Through Chaotic Map Using a Pragmatic Approach - Qazi, Awais Salman; Zahid, Amjad Hussain; Baz, Abdullah; Arslan, Farrukh; Ali, Mubashir; Ali, Jehad (IEEE Access, 2024)
In present-day data communication, the imperative to safeguard information and shield it from a multitude of potential threats and attacks has gained significant prominence. One of the pivotal tools employed in the pursuit of data protection is the design of robust substitution boxes (S-Boxes). These S-Boxes often find their roots in the realm of chaotic maps, leveraging the inherent unpredictability and complexity of these mathematical constructs. An S-Box is an integral and critical component in the design of modern ciphers offering a means to enhance the security of data by introducing non-linearity and confusion into the encryption process. In this research endeavor, we propose the development of a novel chaotic map to create an S-Box that exhibits a notably high nonlinear score making it more formidable for potential adversaries to decrypt the ciphertext. To substantiate the efficacy of the proposed S-Box, a comprehensive analysis is done by comparing its performance using standard criteria including nonlinearity (NL), strict avalanche criterion (SAC), bit independence criterion (BIC), presence of fixed points (FP), linear probability (LP), differential probability (DP), etc. to other state-of-the-art S-Boxes. The comparative analysis reinforces the security fortitude of the proposed S-Box in meeting the rigorous demands of modern data security and presents a vital contribution to the ever-evolving field of cryptographic techniques and data protection in the digital age.
Keywords: Bifurcation; Chaotic communications; Chaotic map; Cipher; Nonlinearity; Optimisations; Permutation; Pragmatic; S-boxes; Substitution box; chaotic map; Data security; nonlinearity; permutation; substitution box